Development, characterization and thermo-regulative performance of microencapsulated phase change material included-glass fiber reinforced foam concrete as novel thermal energy effective-building material - Gençel, Osman; Subasi, Serkan; Ustaoğlu, Abid; Sari, Ahmet; Marasli, Muhammed; Hekimoglu, Gokhan; Kam, Erol; Gençel, Osman; Ustaoğlu, Abid (Pergamon-Elsevier Science Ltd, 2022)
Thermal energy storage (TES) materials present very crucial role for heating and cooling load of building envelopes. This investigation focused on manufacturing of novel TES materials as a lightweight concrete by integration of microencapsulated PCM (MPCM) with foam concrete (FC) to improve thermal mass of buildings. Novel hybrid building material design is presented by combining static insulation property of FC and dynamic thermoregulation property of MPCM. In production of MPCM-included innovative FC, MPCM was used at 5%, 10% and 15% by weight. MPCM increased bulk density up to 592.1 kg/m(3), compressive strength up to 2.52 MPa and thermal conductivity up to 0.153 W/mK. Fourier transform infrared spectroscopy (FTIR) analysis confirmed that any chemical interaction did not occur between MPCM and ingredients of FC. Onset melting temperature and energy storage capacity were measured as 11.88 degrees C and 204 J/g for MPCM and 12.27 degrees C and 30.8 J/g for FC-MPCM, respectively. Center temperature of room with MPCM impregnated foamed concrete became about 1.9 degrees C lesser according to reference room through daytime. Moreover, it achieved about 1.72 degrees C higher room center temperature after sunset hour. Advantageous physico-mechanic and thermal properties make FC-MPCM as promising energy effective material for manufacturing thermo-regulative building components. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Foam Concrete; Microencapsulated Phase Change Material; Thermal Energy Storage; Energy Saving